Clinical measures of disease in adult non-CF bronchiectasis correlate with airway microbiota composition. Issue 8 (6th April 2013) - Rogers, Geraint B; van der Gast, Christopher J; Cuthbertson, Leah; Thomson, Serena K; Bruce, Kenneth D; Martin, Megan L; Serisier, David J
Abstract : Rationale: Despite the potentially important roles for infection in adult non-cystic fibrosis (CF) bronchiectasis disease progression, the bacterial species present in the lower airways of these patients is poorly characterised. Objectives: To provide a comprehensive cross-sectional analysis of bacterial content of lower airway samples from patients with non-CF bronchiectasis using culture-independent microbiology. Methods: Paired induced sputum and bronchoalveolar lavage samples, obtained from 41 adult patients with non-CF bronchiectasis, were analysed by 16S ribosomal RNA gene pyrosequencing. Assessment of species distribution and dispersal allowed 'core' and 'satellite' bacterial populations to be defined for this patient group. Microbiota characteristics correlated with clinical markers of disease. Measurement and main results: 140 bacterial species were identified, including those associated with respiratory tract infections and opportunistic infections more generally. A group of core species, consisting of species detected frequently and in high abundance, was defined. Core species included those currently associated with infection in bronchiectasis, such as Pseudomonas aeruginosa, Haemophilus influenzae and Streptococcus pneumoniae, and many species that would be unlikely to be reported through standard diagnostic surveillance. These included members of the genera Veillonella, Prevotella and Neisseria . The comparative contribution of core and satellite groups suggested a low level of random species acquisition. Bacterial diversity was significantly positively correlated with forced expiratory volume in 1 s (FEV1 ) and bacterial community composition similarity correlated significantly with FEV1, neutrophil count and Leicester cough score. Conclusions: Characteristics of the lower airways microbiota of adult patients with non-CF bronchiectasis correlate significantly with clinical markers of disease severity.